Pengaruh Sustainable Leadership terhadap Sustainable Performance dengan Mediasi Variabel Social Innovation - Anggraini, Ratih; Phang, Selina; Sudhartio, Lily (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research was conducted with the aim of seeing the influence of Sustainable Leadership on Sustainable Performance with the mediation of Social Innovation. Research methodology: The method used in this research was a quantitative method with questionnaire to collect data. The population consisted of manufacturing companies in Batam. The questionnaire was distributed through google forms and hypothesis testing was performed using a Structural Equation Model (SEM). Results: The results of this research show that Sustainable Leadership has a significant and positive influence on Social Innovation, Social Innovation has a significant and positive influence on Sustainable Performance, Sustainable Leadership has a significant and positive influence on Sustainable Performance and Sustainable Leadership has a positive and significant influence on Sustainable Leadership with the mediation of Social Innovation. Conclusion: The study concludes that sustainable leadership has a significant impact on sustainable performance, with social innovation serving as a mediating variable. The findings highlight the importance of integrating leadership practices focused on sustainability to enhance long-term organizational performance through innovation in social practices. Limitations: This research didn’t use a larger sample size and multiple data sources to validate these empirical findings. Contribution: This research contributes to the development of academic knowledge also by integrating sustainable research development, higher education, leadership and innovation.